Atypical Ductal Hyperplasia and Those Bordering on Ductal Carcinoma In Situ Should Be Included in the Active Surveillance Clinical Trials. Issue 1 (11th October 2019) - Khoury, Thaer; Jabbour, Nashwan; Peng, Xuan; Yan, Li; Quinn, Marie
Abstract: Objectives: Women with atypical ductal hyperplasia (ADH), unlike those with ductal carcinoma in situ (DCIS), are denied eligibility for active surveillance clinical trials. Methods: We applied the inclusion criteria of the Comparison of Operative to Monitoring and Endocrine Therapy (COMET) trial to the cases of women (n = 165) at the Roswell Park Cancer Institute who had a diagnosis of ADH, ADH bordering on DCIS, or low- to intermediate-grade DCIS on core biopsy taken during screening mammography. Upgrade of lesions to high risk was based on invasive carcinoma, high-grade DCIS, or DCIS with comedo necrosis. Results: In total, nine (5.5%) lesions were upgraded: two (1.7%) reported ADH, one (5.9%) reported ADH bordering on DCIS, and six (19.4%) reported DCIS ( P = .002); and two (1.6%) reclassified ADH vs seven (17.1%) reclassified DCIS ( P < .001). In multivariate analysis, only increased number of foci had the potential to predict high risk (odds ratio: 1.39; P = .06). Conclusions: We conclude that ADH and ADH bordering on DCIS have lower upgrade rates than DCIS. We recommend opening an active surveillance clinical trial for women with these diagnoses.